Risolvere senza la tecnica X sostituzione.
∫((x^2 + 3·x + 1)·e^(1 - x)) dx =
=e·∫(e^(-x)·(x^2 + 3·x + 1)) dx =
=e·(∫(x^2·e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx=
=e·(- x^2·e^(-x) + 2·∫(x·e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx =
=e·(- x^2·e^(-x) + 2·(- x·e^(-x) + ∫(e^(-x)) dx + ∫(3·x·e^(-x)) dx + ∫(e^(-x)) dx=
=e·(- x^2·e^(-x) + 2·(- x·e^(-x) - e^(-x)) + ∫(3·x·e^(-x)) dx + ∫(e^(-x))dx =
=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·∫(x·e^(-x))dx + ∫(e^(-x)) dx =
=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·(- x·e^(-x) + ∫(e^(-x)) dx + ∫(e^(-x)) dx =
=e·(- (x^2 + 2·x + 2)·e^(-x) + 3·(- x·e^(-x) - e^(-x)) + ∫(e^(-x)) dx =
=e·(- (x^2 + 5·x + 5)·e^(-x) - e^(-x))=
=- e^(1 - x)·(x^2 + 5·x + 6)
Valutato in x = 1
- e^(1 - 1)·(1^2 + 5·1 + 6) = -12
Valutato in x = -2
- e^(1 - (-2))·((-2)^2 + 5·(-2) + 6) = 0
Risultato: -12